Toxicity and residual effects of Diflubenzuron against field and susceptible strains of Spodoptera littoralis (Boisd.) - El-Ghariani, Ibrahim M.; Tabet, Ali B. (Al-Mukhtar Journal of Sciences, 1998)
The effectiveness of Diflubenzuron against the larval instars of both field and susceptible strains of cotton leaf worm , Spodoptera littoralis (Boisd.) was studied. The experimental newly ecdysed larvae were fed on castor bean oil leaves treated with Diflubenzuron for 48 hours. In addition the residual effect of the tested compound on the 4th instar larvae was also manifested. The results showed that the mortality percentages of all tested concentrations almost increased with increasing the concentrations. The field strain more tolerant to the tested compound than the susceptible one. Moreover, data indicated that Diflubenzuron has a residual activity on moulting , pupation, adult emergence, number of eggs and percentage of egg hatching of the treated 4th instar larvae of cotton leaf worm.